Building Fire: Experimental and Numerical Studies on Behaviour of Flows at Opening - Philippe Onguene Mvogo; Ruben Mouangue; Justin Tégawendé Zaida; Marcel Obounou; Henri Ekobena Fouda (Journal of Combustion)
Compartment fire is conducted by complex phenomena which have been the topics of many studies. During fire incident in a building, damage to occupants is not often due to the direct exposition to flames but to hot and toxic gases resulting from combustion between combustibles and surrounding air. Heat is therefore taken far from the source by combustion products which could involve a rapid spread of fire in the entire building. With the intention of studying the impact of the opening size on the behaviour of fire, experimental and computational studies have been undertaken in a reduced scale room including a single open door. Owing to Froude modelling, the obtained results have been transposed into full scale results. In accordance with experiments, numerical studies enabled the investigation of the influence of the ventilation factor on velocities of incoming air and outgoing burned gases and on areas of the surfaces crossed by these fluids during full-developed fire. Comparison of the deduced mass flow rates with the literature reveals an approval agreement.